Students’ Difficulties in Reading Comprehension - Muchasanah Nur Balqis (English LAnguage Study and TEaching, 2022)
Reading is one of the most challenging language skills for many students. They often find it difficult to comprehend a text they are reading, while in fact, reading comprehension is the indicator that one has mastered reading skill. The aims of this study were to find out the factors behind the difficulties faced by the students of SMP Negeri 16 Banda Aceh in reading comprehension. This was a case study using quantitative descriptive method. The result showed that difficulties frequently faced by the students in comprehending a text were their unfamiliarity with a complex word or vocabulary, difficulty in comprehending sentences, difficulty in comprehending a paragraph, difficulty in comprehending the whole selection or content of a text, and the difficulty in identifying the main idea, the plot of a text, the kinds of texts, and English structure without the help of a dictionary.